The Effect of Ultrasonication on the Quality of Keratin Extraction Based on Ionic Liquid from Duck Feather - Senja Salzanabila Putri Perdana; Nita Kusumawati; Maria Monica Sianita Basukiwardojo; Pirim Setiarso; Gina Noor Djalilah; Khofifatul Rahmawati (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
This study investigates the effect of ultrasonic-assisted extraction (UAE) and solvent extraction (SE) on keratin recovery from duck feathers using sodium sulfide-based ionic liquids under different pH conditions. The results showed that SE at acidic pH (pH=3) achieved the highest yield (92%), whereas UAE showed lower recovery (28%) under mildly acidic conditions (pH=5). Spectroscopic and electrophoretic analyses using FTIR confirmed the β-sheet structure with characteristic peaks at 3400 cm−1 (O–H and N–H stretching) and 1660 cm−1 (C=O stretching). Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis analysis (SDS-PAGE) revealed protein bands in the 15–25 kDa range, typical of β-keratin, with higher intensity in SE. Morphological analysis using SEM revealed finer and more homogeneous particles for UAE, while SE produced denser aggregates. Thermal analysis revealed two main degradation stages, occurring at 0–100 °C and 250–500 °C, with UAE samples exhibiting lower residual mass (5.46%) than SE (8.65%). Particle size analysis showed UAE samples had larger but more uniformly distributed particles. XRD results confirmed semi-crystalline structures, with UAE increasing amorphous content and SE maintaining crystallinity. These findings highlight the complementary advantages for tailoring keratin properties toward diverse applications.